Analysis of instrumented scratch hardness and fracture toughness properties of laser surface alloyed tribological coatings. Issue 4 (March 2018) - Misra, Debjit; Shariff, S.M.; Mukhopadhyay, Suman; Chatterjee, Satyajit
Abstract: The mechanical characteristics of ceramic matrix composite (CMC) coatings are widely different from the same materials in bulk form or the individual constituents and are very important to be assessed to carry out application oriented studies on CMC coatings with novel compositions. In the present work, a composite coating of TiB2, TiN and SiC is fabricated in-situ through a combination of high temperature chemical reaction and laser surface alloying. The formation of the surface layer is due to the laser-assisted chemical reaction followed by laser melting. A mixture of TiO2, SiO2, hBN and graphite in stoichiometric proportions is used as the precursor for the chemical reaction. The presence of all the reaction products in the CMC coatings developed is confirmed by X-ray diffraction (XRD) and high resolution transmission electron microscopy (HRTEM). A thorough evaluation of various mechanical properties achieved more insight into the CMC coatings developed. Hardness and fracture toughness of the coatings are measured with a scratch tester. The property evaluations are performed in a similar way for two more coatings fabricated with precursor mixtures containing more than a stoichiometric amount of SiC and hBN respectively. For comparison, a number of composites fabricated through various other routes are characterized afresh with the same set of techniques. Coatings formed with SiC in precursor show higher values of scratch hardness (14.37 GPa), microhardness (24.37 GPa) and fracture toughness (6.63 MPa-m 1/2 ).